Cayman Islands : Assessment of the Supervision and Regulation of the Financial Sector-Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2005)
This paper highlights key findings of the assessment of financial sector regulation and supervision in the Cayman Islands. The assessment reveals that in the last two years, an extensive program of legislative, rule, and guideline development in the Cayman Islands has introduced an increasingly effective system of regulation, both formalizing earlier practices and introducing enhanced procedures. The implementation of financial regulation and supervision complies broadly with standards in all the areas assessed. However, issues related to resources and potential breaches of operational autonomy affect the regulator and, hence, supervision in all sectors.